(untitled) (Journal of International Studies, 2020)
For quite some time now, the Sovereign Wealth Fund (SWF) has become an issue in the front burner of Nigeria’s national debate. The manner it was handled by the federal government became suspicious because there was serious disagreement among the stake holders, starting with the source of funding. But the whole idea of SWF in itself has remained controversial especially with regard to the problem it is meant to solve. The paper makes a contribution to this debate with an analysis of the extant literature and theoretical framework. It cites examples of successful experiences of the SWF and the circumstances that back up their results and suggests that Nigeria’s search for a stable economic order does not lie in the SWF but more importantly to take care of all the necessary structural changes and erect a new political framework for a viable and durable economic development.